Distancing Measures in COVID-19 Pandemic: Loneliness, More than Physical Isolation, Affects Health Status and Psycho-Cognitive Wellbeing in Elderly Patients with Chronic Obstructive Pulmonary Disease. (4th July 2021) - Scarlata, Simone; Cardaci, Vittorio; Santangelo, Carmen; Matarese, Maria; Cesari, Matteo; Antonelli Incalzi, Raffaele
Abstract: Since the outbreak of the SARS-CoV-2 pandemic in 2020, many governments have been imposing confinement and physical distancing measures. No data exist on the effects of lockdowns on the health status of patients affected by chronic pathologies, specifically those with Chronic Obstructive Pulmonary Disease (COPD). Our study aims to establish variations across the psychological and cognitive profile of patients during the isolation period in Italy, in a cohort of patients affected by COPD, between February and May 2020. Forty patients with established COPD were comprehensively evaluated by geriatric multidimensional assessment before the spread of the epidemic in Italy, and submitted to a second evaluation during the subsequent lockdown. We assessed functional ability, basic and instrumental Activities of Daily Living (ADL and IADL), cognition and mood status. We compared the scores obtained at baseline against those obtained during the pandemic, and used mean differences for correlation with major clinical and functional indexes. The score differences from MMSE, ADL and IADL were statistically significant. Such differences were correlated to the presence of a caregiver and to the total number of family members living together. Remarkably, the loneliness dimension, more than the restrictions themselves, seemed to represent the major determinant of altered health status and depressed psycho-cognitive profile in our population. Also remarkably, we detected no correlation between the score variation and the respiratory function indexes of disease severity. The isolation measures adopted during the SARS-CoV-2 pandemic have triggered the classic clinical string associated to geriatric isolation, which leads to a deterioration of cognitive functions, independence and frailty levels in a population affected by a chronic degenerative disease, such as COPD. If considered from a multidimensional geriatric point of view, the individual benefit of isolation measures could be small or non-existent.